2009
DOI: 10.7205/milmed-d-03-9008
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implications of Reduced Binge Drinking Among the Military Health System’s TRICARE Prime Plan Beneficiaries

Abstract: This study examines the economic burden of alcohol misuse to the Department of Defense (DoD) and the benefits of reduced binge drinking among beneficiaries in the DoD's TRICARE Prime plan. Data analyzed include administrative records for approximately 3 million beneficiaries age 18 to 64, DoD's Survey of Health Related Behaviors Among Military Personnel, and the National Survey on Drug Use and Health. Alcohol misuse among Prime beneficiaries cost the DoD an estimated $1.2 billion in 2006--$425 million in highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…However, problem drinking may be particularly costly among military personnel via decreased performance (Frone, 2006;Harwood et al, 2009;Lamond and Dawson, 1999;O'Brien and Lyons, 2000), adverse physical health outcomes (Harris et al, 2009;Williams et al, 2012), comorbid mental health disorders (Milliken et al, 2007), and risk of suicide (LeardMann et al, 2013). Remitting and relapsing problem drinking may be particularly risky among military personnel because it may reflect disordered drinking, which is often difficult to control and change once developed (National Center on Addiction and Substance Abuse, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, problem drinking may be particularly costly among military personnel via decreased performance (Frone, 2006;Harwood et al, 2009;Lamond and Dawson, 1999;O'Brien and Lyons, 2000), adverse physical health outcomes (Harris et al, 2009;Williams et al, 2012), comorbid mental health disorders (Milliken et al, 2007), and risk of suicide (LeardMann et al, 2013). Remitting and relapsing problem drinking may be particularly risky among military personnel because it may reflect disordered drinking, which is often difficult to control and change once developed (National Center on Addiction and Substance Abuse, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Problem drinking may be particularly costly in this population due to associated decreased work performance (Blume et al, 2010;Frone, 2006;Harwood et al, 2009), impaired athletic performance (O'Brien and Lyons, 2000), increased risk of injury (Harris et al, 2009;Williams et al, 2012) and comorbid mental health disorders (Bray et al, 2010;LeardMann et al, 2013),and multiple other adverse health outcomes including sleep deprivation and fatigue (Lamond and Dawson, 1999;Roth and Roehrs, 1996) that may lead to performance impairment (Harwood et al, 2009;Institute of Medicine, 2012). The costs of alcohol use to the Department of Defense (DoD) were recently estimated at $425 million per year (Dall et al, 2007;Institute of Medicine, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It can lead to risky sexual activity, accidents, violence, and other serious consequences. Alcohol misuse is linked to a variety of adverse outcomes in the military and is a costly problem for DoD (Dall et al, 2007;Harwood et al, 2009).…”
Section: Alcoholmentioning
confidence: 99%
“…6 In 2006, alcohol misuse among TRICARE Prime beneficiaries cost the Department of Defense (DoD) an estimated $1.2B; $425M in higher medical costs and $745M in reduced readiness and misconduct charges. 7 Multiple approaches to reducing alcohol misuse and problem drinking exist. Meta-analyses have demonstrated that policies regulating the environment in which alcohol is marketed, particularly its price and availability, and enforced legislative measures to reduce impaired driving are effective in reducing alcohol-related harm.…”
Section: Introductionmentioning
confidence: 99%